Davy loves his mommy - Weninger, Brigitte; Rushton, Andrew (North South, 2014)
Resolving to find the perfect Mother's Day gift for his mother after arriving late for dinner, Davy the exuberant bunny realizes that the best gift of all would be presenting five well-behaved, clean and polite siblings on mom's big day.